Effect of Green Cowpea Manure on the Quality Properties of Sandy Soils Under the Specific Conditions of the Dry Climate in Romania - Reta Drăghici; Ștefan Nanu; Aurelia Diaconu; Cristina Bîrsoghe; Florentina Netcu; Alina Nicoleta Paraschiv; Milica Dima (Agronomy)
This study was carried out on the rotation of cowpea-rye + cowpea in successive crops for green manure-sorghum grains, with the objective of increasing the fertility of sandy soils by incorporating green cowpea manure into the soil in combination with chemical fertilization with NPK. In this sense, after harvesting the rye plant, the cowpea was sown, which was then incorporated into the soil during the formation of the beans in the pod. Before incorporating the cowpea biomass into the soil, the initial fertility status of the soil was assessed, and in the spring, the soil was sown with sorghum grain in two fertilization variants (N80P80K80 and N150P80K80). The soil chemical analyses carried out at the end of the vegetation cycle of the sorghum plant showed that by incorporating 52.4 t/ha green cowpea biomass (9.24 t/ha dry biomass), the quality properties of the soil were significantly improved, with annual increases of 0.17–0.29 g/kg in total nitrogen, 9.5–13.33 mg/kg in extractable phosphorus, 11.33–24 mg/kg in exchangeable potassium, and 0.08–0.12 g/kg in organic carbon, also depending on the sorghum fertilization system. It has also been shown to reduce the acidity of the soil pH and improve the water holding capacity of the soil.